2021
DOI: 10.1136/bmjopen-2020-045707
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous liposomal amphotericin B efficacy and safety for cutaneous and mucosal leishmaniasis: a systematic review and meta-analysis protocol

Abstract: IntroductionTreatment of cutaneous and mucosal leishmaniasis (CL and ML, respectively) must be individualised as there is no universal therapeutic approach. Intravenous liposomal amphotericin B (L-AmB) is an accessible and relatively safe treatment that has been increasingly used for the treatment of CL and ML. While several descriptive studies have been published on the efficacy and safety of L-AmB, there are no interventional studies. Moreover, the findings from published studies have not yet been integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…This systematic review has been registered in the PROSPERO database (registration number CRD42020173440) and was prepared in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 10 ]. The systematic review protocol was published in BMJ Open [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review has been registered in the PROSPERO database (registration number CRD42020173440) and was prepared in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [ 10 ]. The systematic review protocol was published in BMJ Open [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…), doses of liposomal AmB may reach up to 60 mg/kg [ 429 ]. A systematic review of the use of liposomal AmB for the treatment of visceral leishmaniasis has shown evidence not only of its efficacy but, more importantly, of its safety, even in the case of very high doses [ 430 ]. In another recent retrospective study, the different AmB formulations were compared for efficacy and safety.…”
Section: Clinical Use Of Polyenesmentioning
confidence: 99%
“…[9][10][11] In studies conducted with adult patients, the efficacy of Intravenous (IV) L-AmB in CL treatment ranges from 46% to 100%. 9,[12][13][14][15] It has been stated that the difference in success rates in these treatments depends on the type of causative parasite, the dose, and duration of use of the drug. 12,[14][15][16][17] There are few data on the efficacy and safety of IV L-AmB in pediatric CL patients.…”
Section: Introductionmentioning
confidence: 99%
“…9,[12][13][14][15] It has been stated that the difference in success rates in these treatments depends on the type of causative parasite, the dose, and duration of use of the drug. 12,[14][15][16][17] There are few data on the efficacy and safety of IV L-AmB in pediatric CL patients. 10,17 It has been reported that Leishmania tropica is associated with a low treatment response rate in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation